GAMBAR BILIK 24 JAM PERPUSTAKAAN UTM KUALA LUMPUR - Perpustakaan Universiti Teknologi Malaysia. Unit Promosi, compiler (Kuala Lumpur : Perpustakaan UTM Kuala Lumpur)
A photograph collections of UTM Kuala Lumpur Library new 24 hours study room